Avaliação do efeito da concentração de óxido nítrico na ocorrência de albuminúria em crianças e adolescentes com anemia falciforme - Jéssica Alves de Almeida (2022)
Evaluation of the effect of nitric oxide concentration and eNOS gene polymorphisms on the occurrence of albuminuria in children and adolescents with sickle cell anemia in the state of Minas Gerais. Objective: Sickle cell anemia is an autosomal recessive disease caused by a point mutation in the sixth codon of the beta globin gene, located on chromosome 11. The clinical manifestations of sickle cell anemia are caused by vaso-occlusion and chronic hemolytic anemia. The release of free hemoglobin into the circulation, caused by hemolysis, consumes nitric oxide (NO), leading to a reduction in its bioavailability. The NO pathway modulates the severity of sickle cell anemia, with most vascular symptoms of the disease arising from NO depletion. Microalbuminuria (MA) can affect 30% to 60% of patients with sickle cell anemia, and the prevalence increases with increasing age. The objective of this study was to evaluate the influence of NO levels and eNOS gene polymorphisms on the occurrence of albuminuria in children and adolescents with sickle cell anemia. Materials and methods: A cross-sectional study of 80 children was carried out in a cohort of 555 participants diagnosed with sickle cell anemia or Sβ0 thalassemia by the Minas Gerais Neonatal Screening Program (PTN-MG) and followed up at the outpatient clinic of the Hemocentro de Belo Horizonte of Fundação Hemominas . We selected 35 children with albuminuria and 45 controls, matched by sex and age. Genotyping of the eNOS gene rs1799983 and rs2070744 polymorphisms was performed by real-time PCR. Urinary quantification of nitrate (nitric oxide metabolite) was performed using colorimetric detection. The quantification of microalbuminuria was performed using the turbidimetric method. Clinical and hematological data were taken from medical records. Albuminuria and persistent albuminuria were defined as a urine albumin/creatinine ratio greater than 30 mg/g and 100 mg/g, respectively. Results: The population studied consisted of 80 children diagnosed with sickle cell anemia (HbSS) who did not use hydroxyurea (HU), because it is a medication that influences the level of NO; genotyping of polymorphisms was performed on DNA samples from 66 children. Of the 80 children, 35 (43.8%) were male and 45 (56.3%) were female. The mean age was 11.95 ± 4.89 years. There was no association of rs1799983 and rs2070744 polymorphisms and nitrate level with the occurrence of albuminuria. Additionally, there was no association between rs1799983 and rs2070744 polymorphisms and nitrate levels. The frequency of persistent albuminuria was higher (n=4/12; 33.3%) in children who had the GT or TT genotype of the rs1799983 polymorphism, when compared to children with the GG genotype (n=6/54; 11, 1%) (OR=4.0, 95%CI=0.9–17.4; p=0.074). The frequency of persistent albuminuria was higher (n=7/29; 24.1%) in children who had the TC or CC genotype of the rs2070744 polymorphism, when compared to children with the TT genotype (n=3/37; 8, 1%) (OR=3.6,95%CI=0.8–15.4; p=0.063). The HbF level of children who had the TC or CC genotype of the rs2070744 polymorphism was significantly higher when compared to those who had the TT genotype (p=0.024). There was no significant association between the genotypes of the polymorphisms studied and the levels of total Hb, HCM, MCV, leukocytes, reticulocytes and platelets. Discussion: Although the findings suggest that the T allele of SNP rs1799983 and C allele of SNP rs2070744 may be related to the occurrence of persistent albuminuria in children with sickle cell anemia, additional studies with a larger number of participants are necessary to clarify the influence of polymorphisms in the gene eNOS in the occurrence of sickle cell nephropathy. Conclusion: There was no association between urinary nitrate levels, rs1799983 and rs2070744 polymorphisms and the occurrence of albuminuria or persistent albuminuria in children with sickle cell anemia in the state of Minas Gerais.